2011
DOI: 10.4184/asj.2011.5.4.258
|View full text |Cite
|
Sign up to set email alerts
|

Guidewire Breakage: An Unusual Complication of Anterior Odontoid Cannulated Screw Fixation

Abstract: The preferred treatment of a type II odontoid fracture is anterior odontoid screw fixation to preserve the cervical spine range of movement. This case report describes an unusual complication of guidewire breakage during anterior odontoid cannulated screw fixation for a 52-year-old patient who presented with a type II odontoid fracture after a motor vehicle accident. The distal segment of the guidewire was bent over the tip of the cannulated odontoid screw and broke off during guidewire withdrawal. The three m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Therefore, when a skin incision is made at the lower cervical level (C4-C5 or C5-C6), the required exposure and the relatively blind passage of the screw may be the greatest sources of complications [9]. According to Literature review [4, 10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], about 80% of authors used these levels as entry point to achieve a work corridor to the odontoid fracture (Table 1). Another 20% of authors reported a higher level of cervical approach (C2-C3 or C3-C4).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, when a skin incision is made at the lower cervical level (C4-C5 or C5-C6), the required exposure and the relatively blind passage of the screw may be the greatest sources of complications [9]. According to Literature review [4, 10,11,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], about 80% of authors used these levels as entry point to achieve a work corridor to the odontoid fracture (Table 1). Another 20% of authors reported a higher level of cervical approach (C2-C3 or C3-C4).…”
Section: Discussionmentioning
confidence: 99%
“…The neurological examination was within normal limits. In the literature, there has been only one report documenting similar problem [3] where no attempt was made to retrieve the broken wire citing similar apprehensions. Awake intubation was done with nonreinforced tube using fi beroptic bronchoscope to prevent any motion at the neck.…”
Section: Intra-operative K-wire Breakage During Odontoid Screw Fi Xationmentioning
confidence: 99%
“…This method can effectively and safely treat the disease (Shammas et al, 2008). However, if a guidewire catheter is fractured and dislodged during the operation, many serious complications may occur, such as displacement embolism, bleeding, and vascular dissection (Orief et al, 2011). In particular cases, these complications may be lifethreatening.…”
Section: Introductionmentioning
confidence: 99%